Femtosecond laser‐assisted minimally invasive lamellar keratoplasty for the treatment of advanced keratoconus. (16th February 2022) - Gao, Hua; Liu, Mingna; Li, Na; Chen, Tong; Qi, Xiaolin; Xie, Lixin; Shi, Weiyun
Abstract: Background: To evaluate the initial safety and efficacy of femtosecond laser‐assisted minimal invasive lamellar keratoplasty (FL‐MILK) for advanced keratoconus. Methods: Twenty‐two patients (22 eyes) with advanced keratoconus were included in this prospective study. All the involved eyes underwent FL‐MILK. The femtosecond laser was used to create an intrastromal pocket with a 2.3 mm incision in the recipient cornea. Then a stromal button with a diameter of 9.0 mm and a depth of 200 μm was gently inserted into the intrastromal pocket through the 2.3 mm incision and flattened. No sutures were applied. Follow‐up was conducted for 24 months. Results: Twenty‐two patients completed follow‐up data for 12 months, 16 patients had 24 months follow‐up. No epithelial implantation, infection or allogeneic rejection were observed during the follow‐up. Based on baseline values, postoperative 12 months values and postoperative 24 months values, clinical significantly improvement was recorded in corrected distance visual acuity (CDVA) (0.40 ± 0.18 logMAR vs. 0.30 ± 0.12 logMAR and 0.23 ± 0.13 logMAR), the anterior central corneal elevation (29.14 ± 15.33 μm vs. 14.45 ± 13.75μm and 11.38 ± 8.33 μm), and corneal higher‐order aberrations (3.536 ± 1.503 vs. 2.761 ± 1.517 and 0.994 ± 0.391). Corneal biomechanical properties in all eyes improved significantly. SP‐A1 increased from 48.64 ± 12.87 preoperatively to 87.26 ± 21.01 postoperative 12 months and 88.77 ± 18.26 postoperative 24 months; deformation amplitude (DA) decreased from 1.36 ± 0.15 preoperatively to 1.21 ± 0.12 postoperative 12 months and 1.19 ± 0.19 postoperative 24 months. Conclusions: Initial experience suggests that this minimally invasive transplantation may be a feasible option for advanced keratoconus. A larger cohort and longer follow‐up are required to validate our results and establish long‐term safety and efficacy of the procedure.